Intertwined Spiritualities: Exploring the Acculturation of Sufism and Javanese Mysticism in the Keduk Beji Tradition, Ngawi, Indonesia - Puspa Arum Yasinatul; Briyan Maulana Abadi; Nabila Tussa'banniya (Jurnal Adat dan Budaya Indonesia, 2025)
This research explores the acculturation of Sufi values and Javanes mysticism as manifested in the Keduk Beji tradition in Tawun, Ngawi, East Java. Indonesia. Beyond the aim of honoring ancestors by cleaning the sacred well, this tradition contains profound elements of self-cleansing, meditation and communal prayer, along with with mass chanting of dhikr and other sacred ritual processions. Whel many studies focus on religious syncretism. This research is crucial because it offers a unique insight into how a specific local tradition serves as dynamic vehicle for spiritual transformation and social cohesion amidst the pressures of modernization. The process of writing this article uses a qualitative approach with the type of anthropology. This research applies Peter L.’s social construction theory through the collection of primary and secondary data, aiming to construct a deeper understanding. Berger & Thomas Luckman. This theory consists of subjective reality, symbolic reality, objective reality, as well as extrenalization, objectification and internalization. Then in order to find the main values contained in the “Keduk Beji” tradition using explorative descriptive analysis. The result of the analysis of this article is that the symbolic use of water in these rituals becomes an important element, symbolizing purification and renewal, while reflecting a deep meaning about life and spiritually. The tradition emphasizes the transformative nature of these practices, which not only enhance individual spiritual experiences but also strengthen community bonds through shared beliefs and values. This research highlights the significance of sustaining the tradition in the context of modernization, showing that Keduk Beji continues to serve as a cultural anchor for the local community. By integrating Sufi principles with Javanese mystical practices, this tradition exemplifies the harmonious coexistence of diverse spiritual heritages. Ultimately, the Keduk Beji tradition is described as a vital expression of the rich cultural and religious identity of Javanese society, demonstrating the continued relevance of spirituality in contemporary society and encouraging a deeper understanding of the complexity of faith and culture.